2014
DOI: 10.1057/jors.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

Priority dispatching strategies for EMS systems

Abstract: Emergency medical service (EMS) systems provide urgent medical care and transport. In this study we implement dispatching policies for EMS systems that incorporate the severity of the call in order to increase the survival probability of patients. A simulation model is developed to evaluate the performance of EMS systems. Performance is measured in terms of patients' survival probability, since survival probability more directly mirrors patient outcomes. Different response strategies are evaluated utilizing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…In emergency systems planning, Carter et al [44] showed that defining response areas for each ambulance will decrease the average response time. Bandara et al [39] proposed to incorporate better dispatching rule for ambulances together with defined response areas by ambulance in their future research. Without considering call priorities and operational constraints, the three-level integrated problem is related in a way by considering the ambulance location as a facility, response areas as allocated demand sites, and number of ambulances (at each location) as resource capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In emergency systems planning, Carter et al [44] showed that defining response areas for each ambulance will decrease the average response time. Bandara et al [39] proposed to incorporate better dispatching rule for ambulances together with defined response areas by ambulance in their future research. Without considering call priorities and operational constraints, the three-level integrated problem is related in a way by considering the ambulance location as a facility, response areas as allocated demand sites, and number of ambulances (at each location) as resource capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers studied other dispatch strategies. Bandara et al [39] incorporated call urgency into their proposed dispatch heuristic which assigns the nearest available ambulance for Priority 1 calls and the less busy ambulance for Priority 2 calls. Results from simulation experiments reported an increase in patient survivability, decreased average response time, and higher percentage of Priority 1 calls served within 10 minutes.…”
Section: Dispatch Algorithms (Dynamic)mentioning
confidence: 99%
“…However, it is a requirement on the police to be visible to the public in order to deter crime and hence they must have dynamic positions. A recent study, (Bandara, Mayorga, & McLay, 2014), noted that most ambulance location models involve the rule of dispatching the closest ambulance available to the incident irrespective of the incident severity. It was also noted that this method is not always optimal for minimising average response times (Carter, Chaiken, & Ignall, 1972).…”
Section: Background To Dispatchmentioning
confidence: 99%
“…They also noted that dispatching the closest vehicle is not always optimal. Bandara et al [26] proposed a heuristic algorithm to dispatch ambulances based on priority of the call. Their computational experiments showed that the heuristic improved patient survival rate by 4% while decreasing the average response rate by 2%.…”
Section: Related Literaturementioning
confidence: 99%